Acute eosinophilic pneumonia: a fatal reaction to ado-trastuzumab. Issue 9 (3rd September 2021) - LaMorte, Daniel; Desmond, Daniel; Ellis, John; Lipkowitz, Stanley
Abstract : Ado-trastuzumab emtansine (T-DM1) is a monoclonal antibody drug conjugate approved for the treatment of HER2-positive breast cancers. Presented here is a case report of a patient who developed fatal pulmonary toxicity in the form of acute eosinophilic pneumonia while undergoing treatment with T-DM1. Prior to beginning T-DM1 therapy, this patient had been treated with two HER2-targeted agents (trastuzumab, pertuzumab) per National Comprehensive Cancer Network (NCCN) guidelines. This case represents a novel presentation of toxicity associated with T-DM1 while perhaps demonstrating additive toxicity associated with multiple lines of HER2 targeted therapies.